2010
DOI: 10.1890/08-1375.1
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction of Echinacea angustifolia in fragmented prairie is pollen‐limited but not pollinator‐limited

Abstract: Pollen limitation of plant reproduction occurs in many plant species, particularly those in fragmented habitat; however, causes of pollen limitation are often unknown. We investigated the relationship between pollen limitation and pollinator visitation in the purple coneflower, Echinacea angustifolia (Asteraceae), which grows in the extremely fragmented tall grass prairie of North America. Previous investigations showed that pollen limitation of E. angustifolia increases with plant isolation and decreases with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
90
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 66 publications
(97 citation statements)
references
References 51 publications
7
90
0
Order By: Relevance
“…The higher visitation rates in low‐density patches did not attenuate the potentially deleterious consequences of low mate availability for pollen transfer, as found in other species (Duncan et al. 2004b; Campbell and Husband 2007; Wagenius and Lyon 2010). Similar correlations between pollen loads and plant density have been reported for Limnanthes douglasii rosea (Briscoe Runquist 2013) and for experimental plots of Piriqueta caroliniana, in which the floral constancy of the pollinators may account for the lack of effect of other co‐flowering species on pollen loads and reproductive success at low plant densities (Feldman 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The higher visitation rates in low‐density patches did not attenuate the potentially deleterious consequences of low mate availability for pollen transfer, as found in other species (Duncan et al. 2004b; Campbell and Husband 2007; Wagenius and Lyon 2010). Similar correlations between pollen loads and plant density have been reported for Limnanthes douglasii rosea (Briscoe Runquist 2013) and for experimental plots of Piriqueta caroliniana, in which the floral constancy of the pollinators may account for the lack of effect of other co‐flowering species on pollen loads and reproductive success at low plant densities (Feldman 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other studies found no changes in the reproductive output of plants in fragmented habitats (e.g., Aldrich & Hamrick, 1998;Dick, 2001;Lopes, & Buzato, 2007;Aguirre, & Dirzo, 2008). Fragment size may affect plant reproductive output also without any change in pollinator frequency or richness (Ghazoul, 2005;Wagenius, & Lyon, 2010). Plant fertility may be affected by habitat fragmentation indirectly through abiotic changes (Kwak, Velterop, & Andel, 1998), for example, in the light intensity and the availability of water and nutrients in the soil (De Jong, & Klinkhamer, 1989;Saunders, Hobbs, & Margules, 1991).…”
Section: Introductionmentioning
confidence: 97%
“…Since we controlled for the abundance of conspecific plants in each study location, and because only one site had naturally occurring conspecifics, we conclude that the increased variation in pollen limitation and seed set is most likely explained by distancemediated changes in pollinator occurrence (c.f. Wagenius and Lyon 2010;Delmas et al 2015). In this respect, our experimental stations can be compared with small, isolated plant populations exposed to an increased probability of pollination failure (Aguilar et al 2006;Pauw 2007), which may have negative consequences for long-term population persistence (Broadhurst and Young 2006).…”
Section: Effects Of Landscape Configurationmentioning
confidence: 99%
“…Finally, pollination of wild plants can be affected by other flowering plants at a more local scale (Knight et al 2005;Jakobsson et al 2009;Wagenius and Lyon 2010;Delmas et al 2015). Co-flowering insect-pollinated plants can compete for pollinators or facilitate the pollination of other plants, depending on abundance (Dietzsch et al 2011) and floral traits determining quality and accessibility of floral rewards (Mitchel et al 2009;Carvalheiro et al 2014).…”
Section: Introductionmentioning
confidence: 99%